2006
DOI: 10.1167/iovs.06-0574
|View full text |Cite
|
Sign up to set email alerts
|

Cytokeratin 15 Can Be Used to Identify the Limbal Phenotype in Normal and Diseased Ocular Surfaces

Abstract: Although the expression of K15 and K19 differ in humans and mice, specific staining patterns can be used to characterize the epithelial phenotype in normal and diseased ocular surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
118
2
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(131 citation statements)
references
References 35 publications
8
118
2
3
Order By: Relevance
“…During development, the periderm layer plays an important role in preventing pathological cell adhesions between the epithelial linings of adjacent organs, thus ensuring normal tissue formation. Our IHC examinations confirmed that the limbal stem cell marker K15 was exclusively expressed by the basal epithelial cells and that K13 marked the surface and suprabasal epithelium, as reported previously (Ramirez-Miranda et al, 2011;Yoshida et al, 2006). Also, the entire epithelium of MC-2, including the loose surface layers, expressed K13 and the periderm markers K17 and K19 (Fig.…”
Section: A Periderm Lining In Developing MC Structuressupporting
confidence: 90%
“…During development, the periderm layer plays an important role in preventing pathological cell adhesions between the epithelial linings of adjacent organs, thus ensuring normal tissue formation. Our IHC examinations confirmed that the limbal stem cell marker K15 was exclusively expressed by the basal epithelial cells and that K13 marked the surface and suprabasal epithelium, as reported previously (Ramirez-Miranda et al, 2011;Yoshida et al, 2006). Also, the entire epithelium of MC-2, including the loose surface layers, expressed K13 and the periderm markers K17 and K19 (Fig.…”
Section: A Periderm Lining In Developing MC Structuressupporting
confidence: 90%
“…In contrast, loss of FIH-1 promotes keratinocyte differentiation. Confirming these in vitro findings: (i) an increase in expression of Hes 1 and Hey 2, markers of Notch activity (3,13); (ii) a decrease in expression of p63 and K15, markers of undifferentiated limbal keratinocytes (14,15); and (iii) an increase in PAI-2, a marker of keratinocyte differentiation (16), were observed in the limbal epithelium of mice null for FIH-1. We identify an endogenous mechanism for keratinocytes to regulate FIH-1 levels via micro-RNA-31 (miR-31).…”
mentioning
confidence: 68%
“…Interestingly, these nodules were strongly positive for keratin 14 (K14; Fig. 8F), however, the expression of keratin 15 (K15), which is normally detected in the conjunctival and limbal epithelium (Yoshida et al, 2006), was aberrantly extended into the central corneal epithelium upon expression of E3-catenin (Fig. 8G,H).…”
Section: E3-catenin-upregulated Expression Of Mmp-7 Downregulated Ementioning
confidence: 99%